Ecuador: una estrategia de crecimiento para una bano! economía dolarizada - Montiel, Peter J (2002)
This paper is ahant a strategy of economic growth for a dollarized economy like Ecuador. This strategy, in a first section, consists of institutional market policies, financial policics. technology adaptability (for commercial policy and foreign investment), macroeconomic stabilization policies and productivity growth. In the second and third sections, the causes for economics delay are established. Then, there are propositions to obtain a sustained growth.